COMPANY VALUE IN TERMS OF CAPITAL STRUCTURE, OWNERSHIP STRUCTURE AND COMPANY PROFITABILITY IN MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE INDUSTRY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE IN 2017 – 2019 - Anthoni, Lukman; Sudirman, Ganefo (Journal of Industrial Engineering & Management Research, 2021)
This study aims to examine the relationship between firm value with institutional ownership capital structure and profitability in the company. The data used in this study is the annual report of manufacturing companies in the food and beverage industry sector listed on the Indonesia Stock Exchange in the 2017-2019 period. This study uses quantitative methods. This study uses multiple linear regression analysis tools. The implications of the research are expected to make a positive contribution to all parties. As a consideration for the company in observing the factors that have an influence on the value of the company. This research is also expected to be useful for investors and potential investors in seeing opportunities to increase the value of shares held in manufacturing companies in the food and beverage industry sector listed on the IDX. The regulator can also assess and supervise the factors that affect the value of the company so that the financial statements presented are also able to increase the value of the company, therefore the financial statements issued by the company must have quality so that they can be used as a basis for decision making. Capital structure greatly influences the policies taken in the company's operational activities. In addition, the large percentage of share ownership by professionals will also directly increase the value of the company. Profitability is a real benchmark of a company's value that is used as the basis for many parties, especially investors in determining investment in a company.